Answer:
5 im pretty sure
Step-by-step explanation:
if im right, can you mark me brainliest?
Answer:
Step-by-step explanation:
a reflection followed by a rotation
Given equation :−1/2 (x+2) + 112x = 3
We have -1/2 in front of parenthesis on left side .
It's better to remove fraction in an equation, in order make it easier to solve.
In order to remove 2 from denominator of 2, we need to multiply each and every term by 2.
Multiplying each term in the equation by 2, we get
2* −1/2(x+2) +2* 112x = 2*3.
On simplifying this step, we get
-1(x+2) +224x = 6.
Distributing -1 over (x+2), we get
-x -2 +224x = 6
Combining like terms on left side, -x+224x=223x
223x -2 = 6
Adding 2 on both sides, we get
223x -2+2 = 6+2
223x = 8
Dividing both sides by 223, we get
223x/223 = 8/223.
x= 8/223.
Answer:
Yes, there is enough evidence to say the proportions are the same.
Step-by-step explanation:
Null hypothesis: The proportions are the same.
Alternate hypothesis: The proportions are not the same.
Data given:
p1 = 51% = 0.51
n1 = 200
p2 = 48% = 0.48
n2 = 150
pooled proportion (p) = (n1p1 + n2p2) ÷ (n1 + n2) = (200×0.51 + 150×0.48) ÷ (200 + 150) = 174 ÷ 350 = 0.497
Test statistic (z) = (p1 - p2) ÷ sqrt[p(1-p)(1/n1 + 1/n2) = (0.51 - 0.48) ÷ sqrt[0.497(1-0.497)(1/200 + 1/150)] = 0.03 ÷ 0.054 = 0.556
The test is a two-tailed test. At 0.10 significance level the critical values -1.645 and 1.645
Conclusion:
Fail to reject the null hypothesis because the test statistic 0.556 falls within the region bounded by the critical values.
Answer:
A.28
Step-by-step explanation:
Substitute a with 28 so:
-6+28=22
Then simplify the equation:
22=22